2007
DOI: 10.1111/j.1365-2036.2007.03454.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between reflux oesophagitis and features of the metabolic syndrome in Japan

Abstract: SUMMARY BackgroundThere have been many reports about the relationship between reflux oesophagitis and obesity, but not the metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
121
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(143 citation statements)
references
References 31 publications
16
121
4
2
Order By: Relevance
“…9,[26][27][28][29][30][31][32][33][34][35][36][37][38] A meta-analysis has described that the men/women ratio in the prevalence of reflux esophagitis was 1.57 (95% CI, 1.40-1.76) and the mean age of men with reflux esophagitis was lower than that of women. 7 In a systematic review based on data of 67 056 patients using the PubMed database between 1997 and 2011 (including 12 unbiased population-based studies, 8 studies from Asian countries, 2 studies from Europe, and 1 study from the US), the prevalence of reflux esophagitis was lower in women compared to that men (women: 6.1 ± 1.6%, range: 2.1-16.8%; men: 15.9 ± 2.5%, range: 7.0-28.1%; P < 0.01).…”
Section: Endoscopy-based Studymentioning
confidence: 99%
See 1 more Smart Citation
“…9,[26][27][28][29][30][31][32][33][34][35][36][37][38] A meta-analysis has described that the men/women ratio in the prevalence of reflux esophagitis was 1.57 (95% CI, 1.40-1.76) and the mean age of men with reflux esophagitis was lower than that of women. 7 In a systematic review based on data of 67 056 patients using the PubMed database between 1997 and 2011 (including 12 unbiased population-based studies, 8 studies from Asian countries, 2 studies from Europe, and 1 study from the US), the prevalence of reflux esophagitis was lower in women compared to that men (women: 6.1 ± 1.6%, range: 2.1-16.8%; men: 15.9 ± 2.5%, range: 7.0-28.1%; P < 0.01).…”
Section: Endoscopy-based Studymentioning
confidence: 99%
“…Several studies have also suggested that the incidence of reflux esophagitis increased with aging, with women having the trend to be older than men. 29,30,37,52 Moreover, older women showed more severe reflux esophagitis than older men and the incidence of severe reflux esophagitis tends to be increased higher in postmenopausal women than in men. 29,30 Another endoscopy-based study has reported that the incidence of reflux esophagitis was increased in women after the age of 50 years.…”
mentioning
confidence: 99%
“…An increased gastroesophageal pressure gradient and hiatal hernia development have been reported to be induced by a high intra-abdominal pressure due to abdominal fat accumulation (3)(4)(5)(6)(7), while obesity and a high body mass index (BMI) have repeatedly been demonstrated to be associated with the high prevalence of reflux esophagitis and GERD symptoms (8)(9)(10)(11)(12)(13)(14)(15). In addition, metabolic syndrome, diagnosed by the presence of visceral fat accumulation, dyslipidemia, hypertension, and hyperglycemia, has been demonstrated to correlate with the occurrence of GERD (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Signs and symptoms include swollen gums, deepening of gingival crevices leading to the formation of periodontal pockets, bleeding on brushing, increased spacing between teeth, and loose teeth. Recent studies have indicated that periodontitis is closely correlated with systemic disorders, such as obesity, metabolic syndrome and cardiovascular diseases (19,20), which have also been demonstrated to have a positive relationship with GERD occurrence (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In addi-tion, periodontitis may induce or worsen GERD, since saliva secretion, which is influenced by oral hygiene including the periodontal status, has been demonstrated to be associated with GERD (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…GERD has been becoming more prevalent in Asian populations in recent decades, and although the disease is considered to be a common disorder in both Western and Asian populations, its increasing prevalence in Asia may be due to multiple factors, such as the Westernization of eating habits, decrease in the rate of Helicobacter pylori infection, increased gastric acid secretion and a larger elderly population, as well as other factors (2)(3)(4)(5)(6)(7)(8)(9). High intra-abdominal pressure caused by abdominal fat accumulation has been demonstrated to increase the gastroesophageal pressure gradient and incidence of gastroesophageal reflux, while obesity and a high body mass index (BMI) have repeatedly been reported to be correlated with a high prevalence of reflux esophagitis and symptoms of GERD (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). On the other hand, gender differences related to chronological changes in BMI and the prevalence of GERD have not been investigated in Japanese subjects, although a male predominance has been shown to be related to the frequency of reflux esophagitis and GERD (2-5, 8, 9).…”
Section: Introductionmentioning
confidence: 99%